How to minimise the health risks to athletes who compete in weight-sensitive sports review and position statement on behalf of the Ad Hoc Research Working Group on Body Composition, Health and Performance, under the auspices of the IOC Medical Commission - Sundgot-Borgen, J.; Meyer, N. L.; Lohman, T. G.; Ackland, T. R.; Maughan, R. J.; Stewart, A. D.; Müller, W. (British Journal of Sports Medicine, 2013)
A focus on low body weight and body fat content, combined with regulations in some weight-sensitive sports, are considered risk factors for extreme dieting, eating disorders (EDs) and related health consequences among athletes. At present there are, from a health perspective, no generally accepted optimum values for body weight or percentage of fat mass in different sports and there is no `gold standard` method for body composition assessment in athletes. On the basis of health considerations as well as performance, medical support teams should know how to approach elite athletes who seek to achieve an unrealistic body composition and how to prevent restrictive eating practices from developing into an ED. In addition, these teams must know when to raise the alarm and how to advice athletes who are affected by extreme dieting or clinical EDs. However, there is no consensus on when athletes struggling with extreme dieting or EDs should be referred for specialist medical treatment or removed from competition. Based on the present review, we conclude that there is a need for (1) sport-specific and gender-specific preventive programmes, (2) criteria for raising alarm and `does not start` (DNS) for athletes with EDs and (3) modifications to the regulations in some sports. Further, the key areas for research identified include the development of standard methods for body composition assessment in elite athletes; screening measures for EDs among athletes; development and testing of prevention programmes; investigating the short and long-term effects of extreme dieting; and EDs on health and performance.